2015
DOI: 10.1242/jeb.114967
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and molecular responses of the spiny dogfish shark (Squalus acanthias) to high environmental ammonia: scavenging for nitrogen

Abstract: In teleosts, a branchial metabolon links ammonia excretion to Na + uptake via Rh glycoproteins and other transporters. Ureotelic elasmobranchs are thought to have low branchial ammonia permeability, and little is known about Rh function in this ancient group. We cloned Rh cDNAs (Rhag, Rhbg and Rhp2) and evaluated gill ammonia handling in Squalus acanthias. Control ammonia excretion was <5% of urea-N excretion. Sharks exposed to high environmental ammonia (HEA; 1 mmol −1 NH 4 HCO 3 ) for 48 h exhibited active a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 70 publications
1
22
0
Order By: Relevance
“…2) at the highest seawater ammonia-N concentration (nominally1600 µmol l −1 ) was previously reported in S. acanthias suckleyi exposed to 1000 µmol l −1 (Nawata et al, 2015a), and has also been seen in sharks infused directly with comparable ammonia-N loads (Wood et al, 1995;Nawata et al, 2015b). Very likely, it results from a stimulation of urea-N production by the ornithine-urea cycle in excess of the requirements for ureosmotic homeostasis, perhaps as a strategy to avoid ammonia intoxication (Walsh et al, 2007).…”
Section: Concentration Dependence Of Ammonia-n Uptake and Urea-n Excrsupporting
confidence: 54%
See 3 more Smart Citations
“…2) at the highest seawater ammonia-N concentration (nominally1600 µmol l −1 ) was previously reported in S. acanthias suckleyi exposed to 1000 µmol l −1 (Nawata et al, 2015a), and has also been seen in sharks infused directly with comparable ammonia-N loads (Wood et al, 1995;Nawata et al, 2015b). Very likely, it results from a stimulation of urea-N production by the ornithine-urea cycle in excess of the requirements for ureosmotic homeostasis, perhaps as a strategy to avoid ammonia intoxication (Walsh et al, 2007).…”
Section: Concentration Dependence Of Ammonia-n Uptake and Urea-n Excrsupporting
confidence: 54%
“…The data of Nawata et al (2015a) showing ammonia-N uptake against both P NH3 diffusion gradients and NH 4 + electrochemical gradients at the gills suggest that this is an active transport process. Under normal conditions, the effective permeability of the branchial epithelium to ammonia efflux is even lower than that to urea efflux (Wood et al, 1995), for which there is considerable evidence of active retention (Fines et al, 2001;Wood et al, 2013).…”
Section: Perspectivesmentioning
confidence: 90%
See 2 more Smart Citations
“…In our previous studies on responses to HEA in seawater fish, we had found that NH 4 HCO 3 was preferable to NH 4 Cl because, unlike the latter, it did not acidify the water (Wood and Nawata, 2011;Nawata et al, 2015;De Boeck and Wood, 2015). However, these studies had involved concentrations only up to 1.5 mmol l −1 , whereas in the present study we were using much higher concentrations, so we thought it prudent to investigate both salts.…”
Section: Ventilation Changes In Hagfish Loaded Externally With Ammoniamentioning
confidence: 68%